2005
DOI: 10.1093/toxsci/kfi230
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Toxicity, and Mutagenicity of Particulate and Semivolatile Emissions from Heavy-Duty Compressed Natural Gas-Powered Vehicles

Abstract: Particulate matter (PM) and vapor-phase semivolatile organic compounds (SVOC) were collected from three buses fueled by compressed natural gas. The bus engines included a well-functioning, conventional engine; a "high emitter" engine; and a new technology engine with an oxidation catalyst. Chemical analysis of the emissions showed differences among these samples, with the high emitter sample containing markers of engine oil constituents. PM + SVOC samples were also collected for mutagenicity and toxicity testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…The use of the strains TA98 and TA100 in detecting the mutagens among organic and inorganic pollutants has been established by several workers (Lopez et al 2000;Harrington et al 1983;Meier 1988;Le Curieux et al 1995;Aleem and Malik 2003;Seagrave et al 2005). As is evident from the results, a remarkable decrease in the genotoxic potential of the sample was obtained after it was passed through the immobilized cells of P. fluorescens SM1 strain (Table 6).…”
Section: Ames Fluctuation Test With Water Samples Before and After Trmentioning
confidence: 95%
“…The use of the strains TA98 and TA100 in detecting the mutagens among organic and inorganic pollutants has been established by several workers (Lopez et al 2000;Harrington et al 1983;Meier 1988;Le Curieux et al 1995;Aleem and Malik 2003;Seagrave et al 2005). As is evident from the results, a remarkable decrease in the genotoxic potential of the sample was obtained after it was passed through the immobilized cells of P. fluorescens SM1 strain (Table 6).…”
Section: Ames Fluctuation Test With Water Samples Before and After Trmentioning
confidence: 95%
“…Epidemiologic research over the last 30 years has shown increases in adverse cardiovascular and respiratory outcomes in relation to mass concentrations of particulate matter (PM) ≤2.5 μm or ≤10 μm in aerodynamic diameter (PM2.5 and PM10, respectively). A number of research papers [1][2][3][4][5] have been published that examine the exposure and risk of Polycyclic Aromatic Hydrocarbons (PAHs) and their association with PM2.5, PM10 and ultrafine particles (UFPs). Many PAHs are known carcinogens [6][7][8].…”
Section: Methodsmentioning
confidence: 99%
“…A number of research papers [1][2][3][4][5] have been published that examine the exposure and risk of Polycyclic Aromatic Hydrocarbons (PAHs) and their association with PM 2.5 , PM 10 and ultrafine particles (UFPs). Many PAHs are known carcinogens [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The Salmonella/microsome assay has been used to detect mutagens in samples of cigarette smoke (Roemer et al 2004), diesel exhaust (Seagrave et al 2005), surface waters (Siddiqui and Ahmad 2003;Tabrez and Ahmad 2009;Valente-Campos et al 2009), sewage sludge (Perez et al 2003), and soils (Xiao et al 2006;Brinkmann and Eisentraeger 2008). This bioassay has also been used to identify and characterize various mutagens such as heterocyclic amines in cooked foods (Shishu and Kaur 2003;Sugimura et al 2004).…”
Section: Ames Testmentioning
confidence: 99%